2006
DOI: 10.1038/sj.bjc.6603255
|View full text |Cite
|
Sign up to set email alerts
|

Significance of nerve growth factor overexpression and its autocrine loop in oesophageal squamous cell carcinoma

Abstract: Nerve growth factor (NGF) is overexpressed not only in nervous system, but also in several types of cancers. However, the role of NGF in oesophageal squamous cell carcinoma (OESCC) remains unclear. Here, we show the first evidence of NGF-TrkA autocrine loop and clinical significance of NGF overexpression in OESCC. Immunohistochemical study of 109 OESCC specimens revealed that NGF overexpression, found in 63 out of 109 patients (57.8%), was associated with lymph node metastasis, distant metastasis, higher TNM s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 31 publications
(34 reference statements)
4
29
0
Order By: Relevance
“…There is increasing evidence showing that overexpression of NGF results in enhanced invasiveness of a variety of cancer cells and a worse prognosis (Fuminori et al, 2001;Zhu et al, 2002;Tsunoda et al 2006). Moreover, previous studies found that NGF and its receptor were expressed in ACC tissue, and the expression levels were not the same between the solid and the cribriform-tubular type which was considered less aggressive, compared with the former (Sung et al, 2003;Zhu et al, 2003).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…There is increasing evidence showing that overexpression of NGF results in enhanced invasiveness of a variety of cancer cells and a worse prognosis (Fuminori et al, 2001;Zhu et al, 2002;Tsunoda et al 2006). Moreover, previous studies found that NGF and its receptor were expressed in ACC tissue, and the expression levels were not the same between the solid and the cribriform-tubular type which was considered less aggressive, compared with the former (Sung et al, 2003;Zhu et al, 2003).…”
Section: Discussionmentioning
confidence: 90%
“…Recently, a few experiments have shown that NGF or its receptor is highly expressed in some malignancies with neurotropism such as prostatic carcinoma, and NGF is also specifically elevated in oral squamous cell carcinoma with perineural invasion (Fanburg-Smith and Miettinen, 2001;Fuminori, et al, 2001;Kolokythas et al 2006), indicating that this factor is relevant to neurotropism. In addition, NGF overexpression is associated with lymph node metastasis, distant metastasis, higher TNM stage and lowered survival of patients with squamous cell carcinoma of head and neck (Tsunoda et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Triplicate cultures of the esophageal squamous cell carcinoma cell line OE21 were grown in RPMI-1640, supplemented with 10% fetal bovine serum (FBS), at 37˚C in air with 5% CO 2 . Triplicate cultures of the esophageal squamous cell carcinoma cell lines KYSE-170, KYSE-510, KYSE-1170 (11,12) were grown in Ham's F-12/RPMI-1640 with 2% FBS at 37˚C in air with 5% CO 2 , and SUm/c (12) the same except for 5% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of RNA extracted from each sample was spectrophotometrically measured using a Gene Quanto Pro (Amersham Biosciences, Piscataway, N.J., USA). Then, precisely 5 µg from each of the extracted RNA samples was used for first-strand cDNA synthesis using a first-strand cDNA synthesis kit (GE Healthcare Bio-Sciences Corp., Piscataway, N.J., USA) according to the manufacturer’s instructions as described previously [15]. Specifically, Tris-EDTA solution was added to 5 µg of extracted RNA to adjust each of the reaction mixtures to the final volume of 8 µl and the mixture was denatured in 65°C for 10 min and incubated on ice for 2 min.…”
Section: Methodsmentioning
confidence: 99%